THE USE OF FORECASTING METHODS FOR DETERMINING THE MAIN TRENDS IN THE DEVELOPMENT OF PROFESSIONAL TRAINING SYSTEMS FOR SECOND LANGUAGE TEACHERS OF ROMANIA AND UKRAINE - Korolova Larysa (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2023)
The article highlights the results of the completed research of trends in the development of Romania and Ukraine professional training systems of second language teachers. The purpose of the article is to reveal the features of the use of forecasting techniques to determine the main trends in the development of professional training systems for second language teachers in Romania and Ukraine. The essence of the term “extrapolation” and the concepts “extrapolation approach”, “inverse approach” are defined. The article claims that thanks to the use of a comparative analysis, a systematic approach, the methodology of scenario forecasting and conducting an expert assessment during the research, three ways of developing the trends of higher education in Romania and Ukraine in the field of professional training of foreign language teachers were determined and they were formed in three scenarios: optimistic, neutral and pessimistic. An algorithm for using forecasting techniques to determine the main trends in the development of professional training systems for second language teachers in Romania and Ukraine is presented. A step-by-step content analysis of the main directions of the development of Romania and Ukraine professional training systems of second language teachers is highlighted: historical aspects, content, structure and functions of these systems and features of the modern systems of professional training of second language teachers. The questionnaire procedure of experts from Romania and Ukraine leading institutions of higher education and the results obtained after the questionnaire regarding the main directions of the development of the system of professional training of Romania and Ukraine are presented: its historical aspects, content, structure and functions of this system, features of the modern system of professional training of second language teachers. In the article, the author describes step by step the stages that led to the choice of scenario forecasting methodology. The main types of scenario approach are highlighted. The reason for choosing the scenario forecasting method is substantiated, on the grounds that it allows: classifying the received scenarios into three groups - pessimistic, neutral and optimistic scenarios; making a forecast of probable scenarios for the development of events for higher pedagogical education in Romania and Ukraine for the coming years, each of which will be realized if certain conditions of the present are met; conducting a comparative analysis of the identified scenarios to ensure the possibility of forming a management strategy for the development of the system of professional training of teachers of second language teachers in Romania in the coming years, taking into account the identified trends and minimizing the expected losses in cases where they are unavoidable. The work also presents the stages that were implemented when using the scenario forecasting technique. The trends in the development of the system of professional training of second language teachers in Romania and Ukraine determined during the study were grouped into four groups: historical, trends in the development of the content of professional training of second language teachers, organizational and managerial, methodical and characterized. At the end of the article, it is concluded that the determination of trends in the development of the system of professional training of teachers of second language teachers in Romania and Ukraine made it possible to carry out research and scenario forecasting of the directions of the development of systems of professional training of second language teachers, to present probable scenarios of the development of systems of professional training of second language teachers as a component of higher pedagogical education of both studied countries.